Effects of calcination holding time on properties of wide band gap willemite semiconductor nanoparticles by the polymer thermal treatment method - Alibe, Ibrahim Mustapha; Matori, Khamirul Amin; Sidek, Abdul Aziz; Yaakob, Yazid; Rashid, Umer; Alibe, Ali Mustapha; Mohd Zaid, Mohd Hafiz; Ahmad Khiri, Mohammad Zulhasif (MDPI, 2018)
Willemite is a wide band gap semiconductor used in modern day technology for optoelectronics application. In this study, a new simple technique with less energy consumption is proposed. Willemite nanoparticles (NPs) were produced via a water–based solution consisting of a metallic precursor, polyvinylpyrrolidone (PVP), and underwent a calcination process at 900 °C for several holding times between 1–4 h. The FT–IR and Raman spectra indicated the presence of metal oxide bands as well as the effective removal of PVP. The degree of the crystallization and formation of the NPs were determined by XRD. The mean crystallite size of the NPs was between 18.23–27.40 nm. The morphology, particle shape and size distribution were viewed with HR-TEM and FESEM analysis. The willemite NPs aggregate from the smaller to larger particles with an increase in calcination holding time from 1–4 h with the sizes ranging between 19.74–29.71 nm. The energy values obtained from the experimental band gap decreased with increasing the holding time over the range of 5.39 eV at 1 h to at 5.27 at 4 h. These values match well with band gap obtained from the Mott and Davis model for direct transition. The findings in this study are very promising and can justify the use of these novel materials as a potential candidate for green luminescent optoelectronic applications.